Intraparenchymal Hemorrhage in Preterm Neonates: A Broadening Spectrum - Schellinger, Dieter; Grant, Edward G.; Manz, Herbert J.; Patronas, Nicholas J. (American Journal of Neuroradiology, 1988)
Among 800 neonates screened for cerebral bleeding, perinatal sonography indentified 35 preterm neonates with intraparenchymal hemorrhage (IPH). The observed IPHs were categorized in five general groups: classical grade-IV hemorrhage (16 patients), grade-IV hemorrhage with coexisting but anatomically separate hemorrhages (four patients), grade-IV hemorrhage with later development of secondary parenchymal hemorrhages at distant sites (five patients), hemorrhagic periventricular leukomalacia (four patients), and parenchymal hemorrhage unrelated to grade-IV hemorrhages (six patients). Thirty IPHs had concurrent germinal matrix hemorrhages, but in only 16 patients did the IPH represent an extension of the subependymal hematoma and therefore qualify as pure grade-IV hemorrhage according to the most popular classification. The high concurrence of periventricular leukomalacia (80–100% in most groups) and germinal-matrix-remote IPHs supports the concept that most IPHs in preterm neonates represent secondary hemorrhages into ischemic brain tissue.